2004
DOI: 10.1074/jbc.m311643200
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Factor/c-kit Signaling Promotes the Survival, Migration, and Capillary Tube Formation of Human Umbilical Vein Endothelial Cells

Abstract: c-kit receptor tyrosine kinase is a marker of progenitor cells, which differentiate into blood and/or vascular endothelial cells, and has an important role in the amplification/mobilization of progenitor cells. c-kit is expressed in mature endothelial cells, but its role there is unclear. Stem cell factor, a c-kit ligand, dose-dependently promoted survival, migration, and capillary tube formation of human umbilical vein endothelial cells. These effects mimicked those of vascular endothelial growth factor, exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
177
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(184 citation statements)
references
References 53 publications
7
177
0
Order By: Relevance
“…Activation of c-kit by Wt1 explains the lower c-kit expression in tumours of Wt1 KO animals. c-kit is expressed by human and rodent endothelial cells [36][37][38] , and it has been shown that stem cell factor, a c-kit ligand, stimulated migration and tube formation of human endothelial cells 46 . We demonstrate here that overexpression of c-kit increases migration and tube formation of mouse endothelial cells and partially rescues the disturbed proliferation, migration and tube formation in Wt1 knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of c-kit by Wt1 explains the lower c-kit expression in tumours of Wt1 KO animals. c-kit is expressed by human and rodent endothelial cells [36][37][38] , and it has been shown that stem cell factor, a c-kit ligand, stimulated migration and tube formation of human endothelial cells 46 . We demonstrate here that overexpression of c-kit increases migration and tube formation of mouse endothelial cells and partially rescues the disturbed proliferation, migration and tube formation in Wt1 knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, numerous papers have shown that both c-kit and PDGFR were expressed in endothelial cells, as we have observed in our samples of SCLC tumors. [51][52] Langley et al recently showed that STI571 blocked PDGFR signaling of cultured endothelial cells, suggesting that the in vivo antitumor effect of STI571 could be due to an inhibition of tumor angiogenesis. 53 Our results of in vivo combination therapy were in concordance with those reported in Ewing's sarcoma treated by doxorubicin and STI571.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells play a major role in angiogenesis, and it has been demonstrated that HUVECs are able to form capillarylike structures and maintain the phenotype of endothelial cells in vivo, including angiogenesis. [29][30][31] To investigate whether CM increased the invasive or migratory ability of endothelial cells, HUVECs were incubated with CM. We found that CM induced the invasion and migration of HUVECs (Fig.…”
Section: Inhibition Of Endogenous Autophagy In Bystander Cells Via Thmentioning
confidence: 99%